Pelaksanaan Konsep Patient Centered Care Berdasarkan Perspektif Pasien dan Persektif Perawat - Talahatu, Olivia; Paliyama, Dessy G; Manuhutu, Febby; Wakano, Grace J (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the perceptions of implementing nurses and patients' perceptions of the implementation of patient centered care. It is hoped that through this research there will be a serious evaluation of the implementation of patient centered care at Masohi Hospital, Central Maluku. The method used is a quantitative method. The type of research that will be used is a survey carried out using a descriptive analytical design with a cross sectional approach. The results of the research show that there is an influence of the patient's perspective on the quality of service (patient satisfaction), there is an influence of the nurse's perspective on the quality of service (patient satisfaction) and together there is an influence of the perspective of patients and nurses on the quality of service through patient satisfaction. In conclusion, this research shows that a high proportion of patients and nurses who have a good perspective can increase supervision of service quality, reduce errors, and jointly improve service quality through the level of patient satisfaction. Keywords: Patients, Patient Centered Care, Nurses, Perspective